Reproductive phenology of aquatic macrophytes in the Cerrado-Pantanal ecotone - Simão, Crisley Helena; Alves, Flavio Macedo; Barros, Adriana de; Simão, Polyana Milena; Pott, Arnildo; Aoki, Camila (Acta Botânica Brasílica, 2021)
ABSTRACT Studies of plant phenology have been performed predominantly with terrestrial species and rarely so with aquatic communities. Such plants are fundamental for the aquatic ecosystems, representing a valuable source of resources when they are scarce in terrestrial environments for the fauna. Studies of phenology help to understand the reproduction rhythms of plant communities and provide fundamental support to management and conservation. This study aimed to describe the reproductive phenology of 15 species of aquatic plants and determine how it is related to climatic factors and physicochemical variables of water. Plants were collected every 15 days throughout a single year, from two ponds in the Cerrado-Pantanal ecotone, Central-West Brazil. Species were observed in flower and fruit throughout the year with varying phenophases among life forms (amphibious, emergent, rooted, floating and rooted submerged). Photoperiod stood out among climatic variables for flowering and fruiting times. Phenophases were explained by climatic factors, as well as by physicochemical variables of the water. Nitrogen and pH were the variables most related to the highest number of phenophases of different life forms. Such information is relevant to understanding how physicochemical alterations to water by pollution, eutrophication and siltation, among others, can change the phenology of aquatic macrophytes.